Metagenomic Analysis of the Rumen Microbiome of Steers with Wheat-Induced Frothy Bloat - Pitta, D. W.; Pinchak, W. E.; Indugu, N.; Vecchiarelli, B.; Sinha, R.; Fulford, J. D. (Frontiers in Microbiology, 2016)
Frothy bloat is a serious metabolic disorder that affects stocker cattle grazing hard red winter wheat forage in the Southern Great Plains causing reduced performance, morbidity and mortality. We hypothesize that a microbial dysbiosis develops in the rumen microbiome of stocker cattle when grazing on high quality winter wheat pasture that predisposes them to frothy bloat risk. In this study, rumen contents were harvested from six cannulated steers grazing hard red winter wheat (three with bloat score ‘2’ and three with bloat score ‘0’), extracted for genomic DNA and subjected to 16S rDNA and shotgun sequencing on 454/Roche platform. Approximately 1.5 million reads were sequenced, assembled and assigned for phylogenetic and functional annotations. Bacteria predominated up to 84% of the sequences while archaea contributed to nearly 5% of the sequences. The abundance of archaea was higher in bloated animals (P<0.05) and dominated by Methanobrevibacter. Predominant bacterial phyla were Firmicutes(65%), Actinobacteria(13%), Bacteroidetes(10%) and Proteobacteria(6%) across all samples. Genera from Firmicutes such as Clostridium, Eubacterium and Butyrivibrio increased (P<0.05) while Prevotella from Bacteroidetes decreased in bloated samples. Co-occurrence analysis revealed syntrophic associations between bacteria and archaea in non-bloated while such interactions faded in bloated samples. Functional annotations of assembled reads to Subsystems database revealed the abundance of several metabolic pathways, with carbohydrate and protein metabolism well represented. Assignment of contigs to CaZy database revealed a greater diversity of Glycosyl Hydrolases dominated by oligosaccharide breaking enzymes (>70%) in non-bloated samples. However, the abundance and diversity of CaZymes were greatly reduced in bloated samples indicating the disruption of carbohydrate metabolism. We conclude that mild to moderate frothy bloat results from tradeoffs both within and between microbial domains due to greater competition for substrates that are of limited availability as a result of biofilm formation.